(untitled) (Grande Medical Journal, 2025)
Congenital obstructive uropathy is a major cause of kidney injury in children, with some cases requiring early neonatal intervention. Posterior urethral valve (PUV) is a common cause of congenital obstructive uropathy in male infants. We report the case of a 15 days old male, antenatally diagnosed with bilateral hydronephrosis, presented with vomiting and poor urinary flow. Serum creatinine was 5 mg/dL, indicating Stage 3 AKI (KDIGO criteria). After stabilization, PUV was confirmed and treated with valve ablation via electrofulguration in the neonatal period. As PUV can lead to early renal dysfunction, early diagnosis and timely intervention may preserve kidney and bladder function, but long-term follow-up is essential to assess outcomes.